Women in open source software innovation process: Where are they? - Mahmod, Musyrifah; Md Dahalin, Zulkhairi (Universiti Utara Malaysia Press, 2012)
The Open Source Software (OSS) Innovation process is no more a foreign face in the software development community as it is increasingly being used as a platform for modern software innovation both in the commercial and software research community. Although the concept of freedom is mostly prominent with the OSS innovation process, less than 2% of the contributors are women in this male-dominated area. Minorities, including women, are often ignored in its process. This paper presents the case of lack of participation from women in the OSS innovation process. Lack of participation and contributions from women in OSS innovation creates an imbalanced population in the OSS-based knowledge demography and an unbalanced proportion of gender distribution.Based on a comprehensive review, this paper aims to suggest a Constructivist-Technofeminist-OSS Innovation Process framework for understanding female contributions in OSS innovation, not only from a singular point of technical view, but also from social constructivist and feminist perspectives